Food waste and its associated environmental impacts in workplace buffet-style canteens in Beijing, China - Zhang, Dan; Zhang, Panpan; Xue, Li; Wu, Liang (Frontiers in Sustainable Food Systems, 2024)
Food waste is regarded as a serious global issue due to its adverse impacts on food security, ecosystem services, biodiversity, and human well-being. More attentionhas been paid to this problem in the food service sector. However, limited studies focused on food waste in workplace canteens, especially in workplace buffet-style canteens. We analyzed 656 weighted samples from four buffet-style canteens to investigate food waste and its associated environmental impacts. Our findings revealed that the average daily food waste per person is 158.4 g; specifically, food waste at the lunchtime was 78.8 g per capita, approximately 2.8 times greater than breakfast and 1.5 times higher than dinner. Significant differences were found in the composition of food waste at breakfast, lunch, and dinner, due to the varied dietary cultures and health considerations. Vegetables contributed the largest share of food waste for all three meals, and more livestock food waste was observed at lunch and dinner. The self-run workplace buffet-style canteen had significantly lower food waste than the outsourced canteens for all three meals, while food types and cuisine styles had significantly influenced food waste. Additionally, our research demonstrated that food waste could bring in some environmental issues, considering its ecological, water, carbon, nitrogen, and phosphorus footprints. Moreover, less than 30% of livestock food waste contributed to more than 60% of environmental footprints. The results highlighted that some economic measures could be one of the important strategies for reducing food waste in workplace buffet-style canteens.